PAC1 receptor mRNA and protein distribution in rat and human trigeminal and sphenopalatine ganglia, spinal trigeminal nucleus and in dura mater. (June 2019) - Hensley, Kelly; Pretorius, Jim; Chan, Brian; Page, Keith; Liu, Hantao; Choi, Chang; Shi, Di; Xu, Cen; Edvinsson, Lars; Miller, Silke
Background: To further understand the role of pituitary adenylate cyclase-activating polypeptide 1 (PAC1) receptors in headache disorders, we mapped their expression in tissues of the trigemino-autonomic system by immunohistochemistry and in situ hybridization. Methods: To optimize screening for monoclonal antibodies suitable for immunohistochemistry on formalin-fixed, paraffin-embedded tissues, we developed a new enzyme-linked immunosorbent assay using formalin-fixed, paraffin-embedded cells overexpressing human PAC1 receptors. 169G4.1 was selected from these studies for analysis of rat and human tissues and chimerized onto a mouse backbone to avoid human-on-human cross-reactivity. Immunoreactivity was compared to PAC1 receptor mRNA by in situ hybridization in both species. Results: 169G4.1 immunoreactivity delineated neuronal cell bodies in the sphenopalatine ganglion in both rat and human, whereas no staining was detected in the trigeminal ganglion. The spinal trigeminal nucleus in both species showed immunoreactivity as especially strong in the upper laminae with both cell bodies and neuropil being labelled. No immunoreactivity was seen in either rat or human dura mater vessels. In situ hybridization in both species revealed mRNA in sphenopalatine ganglion neurons and the spinal trigeminal nucleus, a weak signal in the trigeminal nucleus and no signal in dural vessels. Conclusion: Taken together, these data support a role for PAC1 receptors in the trigemino-autonomic system as it relates to headache pathophysiology.